Functional quality and antioxidant properties of tomato genotypes for breeding better quality varieties - R. S. Pal; N. K. Hedau; Lakshmi Kant and; A. Pattanayak (Electronic Journal of Plant Breeding, 2018)
Twenty-two tomato advanced lines were investigated for the functional and antioxidant properties as well as their contents. Wide variations were observed for most of the traits, e.g., total soluble solids (3.50-6.03%), pH (3.90-5.08), pericarp thickness (5.40-8.70mm), fruit firmness (0.418 to 0.959 kg), lycopene content (2.84-9.83 mg/100g fw) and β-Carotene (3.37-8.16 mg/100g FW), indicative of considerable levels of genetic diversity. Highest concentration of ascorbic acid was found in the cultivar VT 1320 (305.59 mg/ kg). Total phenolic content ranged from 0.60 to 1.14 mgGAE/g FW whereas total flavonoids content ranged from 0.99 to 1.75 mgCE/g FW. Total flavonoids, total antioxidant activity, ABTS and DPPH free radical inhibition, total polyphenols and lycopene are having strong positive correlation among themselves. The results of present study are potentially useful for tomato breeders working on the development of new varieties with better quality.